Paris Exposition Grand March - George Maywood-Schleiffarth::::::::: (S. Brainards Sons Co.)
Piano score, 6 p. Cover title: Paris exposition march. By Geo. Schleiffarth. (Maywood.) On cover is birds-eye view of the exposition, printed in pink. At head of title on cover: The first 1900 Paris exposition march published. Publishers advertisement on verso of last leaf.